Patterns of Obesity and Overweight in the Iranian Population: Findings of STEPs 2016 - Djalalinia, Shirin; Saeedi Moghaddam, Sahar; Sheidaei, Ali; Rezaei, Nazila; Naghibi Iravani, Seyed Sina; Modirian, Mitra; Zokaei, Hossein; Yoosefi, Moein; Gohari, Kimiya; Kousha, Ahmad; Abdi, Zhaleh; Naderimagham, Shohreh; et al. (Frontiers in Endocrinology, 2020)
Background: Obesity has become a common health problem all over the world. Benefiting from a national representative sample, the present study aimed to estimate the prevalence of overweight/obesity and the distribution of Body Mass Index (BMI) levels in the Iranian adult population, by sex, age, and geographical distribution. Methods: This was a large-scale national cross-sectional study of Non-Communicable Diseases risk factor surveillance in Iran. Through a systematic cluster random sampling, 31,050 Iranian adult participants aged 18 years and over were enrolled in the study. The main research tools used assessed three different levels of data, namely, 1) demographic, epidemiologic, and risk–related behavioral data; 2) physical measurements; and 3) lab measurements. Anthropometric measurements were taken using standard protocols and calibrated instruments. Results: In 2016, the national prevalence rates of normal weight, obesity and overweight/obesity among Iranian adults were, 36.7% (95% CI: 36.1-37.3), 22.7% (22.2-23.2) and 59.3% (58.7-59.9), respectively. There was a significant difference between the prevalence of obesity among males [15.3% (14.7-15.9)] and females [29.8% (29.0-30.5)], (p≤0.001). The 55-64 [31.5% (30.1-33.0)] and the 18-24 [8.3% (7.3-9.4)] year-old age groups had the highest and lowest prevalence of obesity, respectively. The results show a geographical pattern at provincial level, where the level of BMI increases among populations ranging from the southeastern to the northwestern regions of the country. The highest provincial prevalence of obesity was almost 2.5-fold higher than the lowest provincial prevalence. Conclusion: We found a significant difference between the prevalence of obesity in males and females. Moreover, there was a considerable difference in the geographical pattern of the prevalence of obesity and overweight. Further evidence is warranted to promote the strategies and interventions related to prevention and control of factors associated with weight gain.